(RETRACTED ARTICLE) Effect of artificial light on plant ecology and physiology: A review: This article has been retracted. - BAJYA, MAMTA; BAJAYA, TEJPAL; KAUR, RAVNEET; DAR, SALEEM JAHANGIR; YADAV, SURESH (The Indian Journal of Agricultural Sciences, 2025)
Early in the 20th century, introduction of artificial light has caused a significant change in human developmental process, but use of artificial light in night has also produced negative effect on phonological, physiological and ecological responses which are sustained in the plants, animals and microorganism from millions of years. In these consequences, most of the plant processes under ANLP are affected intensely and cause compelling changes in plant life cycle from germination to maturity. However, severe effects were observed in the case of pollination, photoreceptor signalling, flowering and microhabitats of plants. Along with, drastic effects on ecology and environments, its relevance to human developmental processes cannot be avoided. Therefore, we need to equipoise between sustainable environment and steady human development processes. Further, selection of plant/crop species, which are more responsive to artificial night light pollution, can minimize the ecological consequences of night light pollution. Likewise, changing artificial nightscape with the implication of new Light emitting diodes lightening policies like Ujala, which are low cost, more durable, eco-friendly and less emitter of CO2, have potential to overcome the biodiversity threat, which arises due to the old artificial lightening technology, used from decades. Hence, adopting new advanced artificial lightening technology and understanding its impact on plant ecosystem will be a future challenge for plant biologists. However, drastic effects of artificial light during night time are enormous; therefore, the present topic is focused on the physiological and ecological consequences of artificial night light pollution on plant systems.